KEPENTINGAN NASIONAL INDONESIA UNTUK TIDAK BERGABUNG DALAM TRANS-PACIFIC PARTNERSHIP AGREEMENT (TPP) DI ASIA PASIFIK TAHUN 2011 - Ratnawilis '; ndra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is a qualitative research by conducting literature review and compiling data from books, journal and the website. It’s explains about Indonesia’s rejection on transpacific partnership (TPP) agreementin 2011. TPP Agreement is a concept free trade in Asia Pasifik with the highest rules-based 21stcentury. TPP Agreement is an agenda of America that was submitted on KTT-19 APEC in Honolulu, Hawai Amerika Serikat. It’s on 2010-2011 has nine partner’s members, they are Singapore, New Zealand, Chili, Brunei Darussalam, United State, Vietnam, Peru, Australia, and Malaysia. In analizing all members of TPP are the members of APEC in 2011. According to Indonesia’s ministry of commerce, Gita Wirjawan, Indonesia as APEC’s members rejects to join on TPP agreement.This Indonesia’s rejection on  TPP agreement is influenced by interest group so that this research uses bureaucratic politics theory. Some of interest group in Indonesia support the rejection on TPP.This research shows that Indonesia does not join on TPP agreement because Indonesia has been involved in free trade diplomacy with ASEAN such as  ASEAN-China Free Trade Agreement (ACFTA), ASEANAustralia and New Zealand Free Trade Agreement (AANZFTA), ASEAN Community 2015.Keywords: Indonesia, Trans-pacific Partnership Agreement (TPP), Bureaucratic     Politics, Interest Groups, Free Trade Agreement